The Competence of the Administrative Court and Administrative Justice - Aju - Putrijanti (Universitas Lampung, 2020)
Administrative Court is a specialized court under the Supreme Court with a role to settle the administrative disputes included staffing disputes. The legitimation of Law No. 30 of 2104 concerning Government Administration has brought a new paradigm in the governance framework. Also, the competence of the Court is broader than before. In Addition, some regulations give more competence to the Court. It is normative juridical research. It uses statute, conceptual approach to observed, analyzed and discussion on the issues. This research is to develop the relations between the competence of the Court and administrative justice. Based on the research, broader competence gives more opportunity to get access to justice.In conclusion, administrative justice has some meanings; first, it is the rights of an individual. Therefore, the government has to provide detail, clear information for any individual before issuing a decree based on the application, rights to claims and revision for any mistakes. Second, the defendant must obey and implement the judicial verdict. This obligation as an implementation of administrative justice and legal certainty for Plaintiff and obedience by the Defendant to the judge verdict. Third, administrative justice should be supported by the regulations by obeying the judge verdict. This is part of improving the quality of governance.